Cationic Zinc Hydride Catalyzed Carbon Dioxide Reduction to Formate: Deciphering Elementary Reactions, Isolation of Intermediates, and Computational Investigations. Issue 26 (24th February 2021) - Chambenahalli, Raju; Bhargav, R. M.; McCabe, Karl N.; Andrews, Alex P.; Ritter, Florian; Okuda, Jun; Maron, Laurent; Venugopal, Ajay
Abstract: Zinc has been an element of choice for carbon dioxide reduction in recent years. Zinc compounds have been showcased as catalysts for carbon dioxide hydrosilylation and hydroboration. The extent of carbon dioxide reduction can depend on various factors, including electrophilicity at the zinc center and the denticity of the ancillary ligands. In a few cases, the addition of Lewis acids to zinc hydride catalysts markedly influences carbon dioxide reduction. These factors have been investigated by exploring elementary reactions of carbon dioxide hydrosilylation and hydroboration by using cationic zinc hydrides bearing tetradentate tris[2‐(dimethylamino)ethyl]amine and tridentate N, N, N ′, N ′′, N ′′‐pentamethyldiethylenetriamine in the presence of triphenylborane and tris(pentafluorophenyl)borane. Abstract : Exploring elementary reactions : Cationic zinc hydrides are successfully probed for CO2 reduction. The mechanistic pathways operative in cationic zinc hydride catalyzed hydrosilylation and hydroboration are established through experiments and computations. The coordination number at zinc and secondary Lewis acid dictate the efficacy.